Impact of RSUME Actions on Biomolecular Modifications in Physio-Pathological Processes - Fuertes, Mariana; Elguero, Belén; Gonilski-Pacin, David; Herbstein, Florencia; Rosmino, Josefina; Ciancio del Giudice, Nicolas; Fiz, Manuel; Falcucci, Lara; Arzt, Eduardo (Frontiers in Endocrinology, 2022)
The small RWD domain-containing protein called RSUME or RWDD3 was cloned from pituitary tumor cells with raising tumorigenic and angiogenic proficiency. RSUME expression is induced under hypoxia or heat shock and is upregulated, at several pathophysiological stages, in tissues like pituitary, kidney, heart, pancreas or adrenal gland. Up to date, several factors with essential roles in endocrine-related cancer appear to be modulated by RWDD3. RSUME regulates, through its post-translational (PTM) modification, pituitary tumor transforming gene (PTTG) protein stability in pituitary tumors. Interestingly, in these tumors another PTM, the regulation of EGFR levels by USP8, plays a pathogenic role. Further, RSUME suppresses ubiquitin conjugation to hypoxia inducible factor (HIF) by blocking VHL E3-ubiquitin ligase activity, contributing to the development of von Hippel-Lindau disease. RSUME enhances protein SUMOylation of specific targets involved in inflammation such as IkB and the glucocorticoid receptor. For many of its actions, RSUME associates with regulatory proteins of ubiquitin and SUMO cascades, such as the E2-SUMO conjugase Ubc9 or the E3 ubiquitin ligase VHL. New evidence about RSUME involvement in inflammatory and hypoxic conditions, such as cardiac tissue response to ischemia and neuropathic pain, and its role in several developmental processes, is discussed as well. Given the modulation of PTMs by RSUME in neuroendocrine tumors, we focus on its interactors and its mode of action. Insights into functional implications and molecular mechanisms of RSUME action on biomolecular modifications of key factors of pituitary adenomas and renal cell carcinoma, provide renewed information about new targets to treat these pathologies.